A new photocrosslinkable polycaprolactone‐based ink for three‐dimensional inkjet printing. Issue 6 (14th May 2016) - He, Yinfeng; Tuck, Christopher J.; Prina, Elisabetta; Kilsby, Sam; Christie, Steven D. R.; Edmondson, Stephen; Hague, Richard J. M.; Rose, Felicity R. A. J.; Wildman, Ricky D.
Abstract: A new type of photocrosslinkable polycaprolactone (PCL) based ink that is suitable for three‐dimensional (3D) inkjet printing has been developed. Photocrosslinkable Polycaprolactone dimethylacrylate (PCLDMA) was synthesized and mixed with poly(ethylene glycol) diacrylate (PEGDA) to prepare an ink with a suitable viscosity for inkjet printing. The ink performance under different printing environments, initiator concentrations, and post processes was studied. This showed that a nitrogen atmosphere during printing was beneficial for curing and material property optimization, as well as improving the quality of structures produced. A simple structure, built in the z ‐direction, demonstrated the potential for this material for the production of 3D printed objects. Cell tests were carried out to investigate the biocompatibility of the developed ink. © 2016 The Authors Journal of Biomedical Materials Research Part B: Applied Biomaterials Published by Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1645–1657, 2017.